Wind-tunnel measurements in the wake of a simple structure in a simulated atmospheric flow - Peterka, Jon A., author; Cermak, Jack E., author; Hansen, A. C., author; Fluid Mechanics Program, Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1975)
Measurements of longitudinal mean velocity and turbulence intensity were made in the wake of a rectangular model building in a simulated atmospheric boundary-layer wind. The model building was a 1:50 scale model of a structure used in a wake measurement program at the NASA, George C. Marshall Space Flight Center, 8-tower boundary-layer facility. The approach wind profile and measurement locations were chosen to match the field site conditions. The wakes of the building in winds from azimuths of 0 and 47 degrees referenced to the normal to the building long axis were examined. The effect of two lines of trees upwind of the building on the wake and the importance of the ratio of the building height to boundary-layer thickness on the extent of the wake were determined.
CER73-74ACH-JAP-JEC43a.
For George C. Marshall Space Flight Center, National Aeronautics and Space Administration.
Contract NAS-8-29583.
January 1975.
Keywords: Wind tunnel models; Buildings -- Aerodynamics